2007
DOI: 10.1016/j.peptides.2006.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activation of pro-inflammatory cytokines in mice lacking natriuretic peptide receptor-A

Abstract: Natriuretic peptide receptor-A (NPRA) is the principal receptor for the cardiac hormones ANP and BNP. Mice lacking NPRA develop progressive cardiac hypertrophy and congestive heart failure. However, the mechanisms responsible for hypertrophic growth in the absence of NPRA signaling are not yet known. In the present study, we determined whether deficiency of NPRA/cGMP signaling alters the cardiac pro-inflammatory cytokines gene expression in Npr1 (coding for NPRA) geneknockout (Npr1 −/− ) mice exhibiting cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 34 publications
2
22
1
Order By: Relevance
“…The cardiac walls demonstrate prominent interstitial fibrosis, 32 increased expression of extracellular matrix proteins, 33 and activation of proinflammatory cytokines. 34 With respect to the ventricular phenotype, similar to knockout mice, 6 of our 13 patients had upper limit of normal or increased LV end-diastolic diameter with normal LV function, and most of them showed an increase of the echocardiographic LV mass. Finally, only 2 patients had arterial hypertension; because all patients were treated with renin-angiotensin system inhibitors for the AD, the possibility exists that pressure levels were controlled by chronic treatment with renin-angiotensin system inhibitors.…”
Section: Experimental Modelsmentioning
confidence: 75%
“…The cardiac walls demonstrate prominent interstitial fibrosis, 32 increased expression of extracellular matrix proteins, 33 and activation of proinflammatory cytokines. 34 With respect to the ventricular phenotype, similar to knockout mice, 6 of our 13 patients had upper limit of normal or increased LV end-diastolic diameter with normal LV function, and most of them showed an increase of the echocardiographic LV mass. Finally, only 2 patients had arterial hypertension; because all patients were treated with renin-angiotensin system inhibitors for the AD, the possibility exists that pressure levels were controlled by chronic treatment with renin-angiotensin system inhibitors.…”
Section: Experimental Modelsmentioning
confidence: 75%
“…1,2 Similarly, other investigators have shown that Npr1 Ϫ/Ϫ mice carrying gene-targeted disruption of Npr1 (encoding for the NPRA receptor) exhibit the same phenotype of cardiac hypertrophy and fibrosis as Nppa Ϫ/Ϫ mice and are associated with reduced guanylyl cyclase activity and cGMP levels and increased expression of angiotensinconverting enzyme and angiotensin II, as well as proinflammatory cytokines such as tumor necrosis factor-␣, interleukin-6, and TGF-␤1 in the heart, suggesting that disruption of ANP/NPRA/cGMP signaling leads to increases in cardiac hypertrophic stimuli. 27,28 We have shown that the excess cardiac enlargement and remodeling in Nppa Ϫ/Ϫ mice are a consequence of increased MF transformation and proliferation and deposition of ECM components, rather than excess CM hypertrophy. 1 In contrast, using a novel DnTGF␤RII mouse model, these processes are markedly attenuated by disruption of TGF-␤ signaling in heart.…”
Section: Discussionmentioning
confidence: 97%
“…Systemic deletion of Npr1 gene leads to high blood pressure, cardiac hypertrophy, and congestive heart failure after 6 mo of age (47,64). In the present studies, we utilized 6 mo old age-matched wild-type and Npr1 gene-disrupted mice to examine the consequences of NPRA deletion on proinflammatory responses of NF-B, IKK, and IB␣ in the kidneys of Npr1 null mutant mice.…”
mentioning
confidence: 99%